Eupafolin suppresses TGF-β1-induced human lung fibroblasts differentiation by downregulating β-catenin/plasminogen activator inhibitor-1 signaling - Mei Zhu; Jian Zhang; Xionghua Sun; Xihua Chen; Xiaogang Jiang (Elsevier, 2022)
The anti-fibrotic activity of flavonoids from Eupatorium lindleyanum DC (EL) remains unclear. Our results showed that flavones from the plant exerted a stronger inhibitory effect than flavonols, and eupafolin presented the highest activity on lung fibroblast differentiation. Eupafolin weakened the levels of α-smooth muscle actin, the production of type I collagen and fibronectin, fibroblast-containing gel contractility and microfilament formation in transforming growth factor-β1-induced lung fibroblasts. Interestingly, eupafolin did not affect the canonical TGF-β/Smad2/3 pathway. Eupafolin reduced the levels of plasminogen activator inhibitor-1 (PAI-1), and pharmacological inhibition and knockdown of PAI-1 mitigated the differentiation of lung fibroblasts. Finally, β-catenin agonist, SKL2001, reversed the suppressive effect of eupafolin on PAI-1 expression and lung fibroblast differentiation. Therefore, flavones have higher anti-fibrotic activity than flavonols obtained from EL, and eupafolin suppressed lung fibroblast differentiation by downregulating β-catenin/PAI-1 signaling rather than the canonical TGF-β/Smad2/3 pathway.